Oh, Susanna! - Kane, Joseph, 1894-1975; Drake, Oliver; Autry, Gene, 1907-1998; Burnette, Smiley, 1911-1967; Republic Pictures; Cinetel Films ([Los Angeles, CA] : Republic Pictures, 1936)
Singing cowboy Gene Autry is traveling to Mineral Springs Ranch to visit an old friend, Jefferson Lee, whom he hasn't seen in fifteen years. On the train he is robbed and then thrown from the train by escaped murderer Wolf Benson. Believing Gene to be dead, Wolf plans to travel to Mineral Springs Ranch and pose as the radio celebrity in order to collect the $10,000 that Lee owes Gene. --
Originally released as a motion picture in 1936.
Gene Autry, Smiley Burnette, Frances Grant, Earle Hodgins, Light Crust Doughboys, Champion.
Cinematographer, William Nobles; editor, Lester Orlebeck.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: Train robberies -- Drama; Murderers -- Drama; Western films; Feature films; Internet videos; Streaming video